Implementation of a Bedside Point-of-Care Ultrasound Program in a Large Academic Neonatal Intensive Care Unit - Pai, Vidya V.; Noh, Caroline Y.; Dasani, Reedhi; Vallandingham, Shelby; Manipon, Christine; Haileselassie, Bereketeab; Profit, Jochen; Balasundaram, Malathi; Davis, Alexis S.; Bhombal, Shazia (American Journal of Perinatology, 2022)
Objectives In the adult and pediatric critical care population, point-of-care ultrasound (POCUS) can aid in diagnosis, patient management, and procedural accuracy. For neonatal providers, training in ultrasound and the use of ultrasound for diagnosis and management is increasing, but use in the neonatal intensive care unit (NICU) is still uncommon compared with other critical care fields. Our objective was to describe the process of implementing a POCUS program in a large academic NICU and evaluate the role of ultrasound in neonatal care during early adaption of this program.Study Design A POCUS program established in December 2018 included regular bedside scanning, educational sessions, and quality assurance, in collaboration with members of the cardiology, radiology, and pediatric critical care divisions. Core applications were determined, and protocols outlined guidelines for image acquisition. An online database included images and descriptive logs for each ultrasound.Results A total of 508 bedside ultrasounds (76.8% diagnostic and 23.2% procedural) were performed by 23 providers from December 2018 to December 2020 in five core diagnostic applications: umbilical line visualization, cardiac, lung, abdomen (including bladder), and cranial as well as procedural applications. POCUS guided therapy and influenced clinical management in all applications: umbilical line assessment (26%), cardiac (33%), lung (14%), abdomen (53%), and cranial (43%). With regard to procedural ultrasound, 74% of ultrasound-guided arterial access and 89% of ultrasound-guided lumbar punctures were successful.Conclusions Implementation of a POCUS program is feasible in a large academic NICU and can benefit from a team approach. Establishing a program in any NICU requires didactic opportunities, a defined scope of practice, and imaging review with quality assurance. Bedside clinician performed ultrasound findings can provide valuable information in the NICU and impact clinical management.Key Points
Keywords: bedside ultrasound; POCUS; program development; ultrasound program